Liver Transplant Complications—A Pictorial Review - Ethiraju, Vijayakumaran; Arunachalam, Venkatesh Kasi; Vijayaragavan, Paari; Poyyamoli, Santhosh; Kumar, Rajesh; Rajasekaran, Sriman; Mahadevan, Gowtham Sembagoundenvalasu; Cannane, Seetharaman; Arunachalam, Pudhiavan; Ramasamy, Rajkumar; Kumar, Harish; Selvaraj, Swathigha; Kashyap, Ravindar; Venkatesh, Karthick; Mehta, Pankaj; Cherian, Mathew (Indographics, 2023)
Liver transplantation is the most definitive treatment for decompensated chronic liver diseases, acute hepatic failure, and localized hepatocellular carcinomas. With the widespread use of extensive preop evaluation and advanced surgical techniques, the success rate of liver transplantation has dramatically risen over the decade. In a world of increasing demand for liver donors from brain dead donors, a rising trend is seen in the acceptance of living donor liver transplantation procedures. However, postoperative surveillance needs a lower threshold for early imaging to identify the most dreaded complications for salvaging the graft. This pictorial essay aims to categorize the postliver transplantation complications and various imaging findings to diagnose them. The complications can be broadly classified into vascular and nonvascular complications. The most important concern among vascular complications is hepatic artery thrombosis, which frequently results in graft failure. The nonvascular complication comprises biliary origin, infection, and immune response. Multimodality imaging is the need of the hour, which includes ultrasound as the primary tool for gross evaluation, followed by triphasic computed tomography and magnetic resonance imaging (MRI). Newer techniques in MRI, like diffusion-weighted imaging, arterial spin labeling, diffusion kurtosis imaging, blood oxygenation-level dependent, and magnetic resonance elastography, can also be used to diagnose these complications. Interventional management through minimal access has become the first line of management in certain vascular and nonvascular complications, which can salvage the graft.
Keywords: liver transplantation; thrombosis; biliary strictures; interventional radiology